The relationship between presence of meaning and life satisfaction among Chinese young adults: a moderated mediation model of perceived stress and hope - Zhang, Yan; Jiang, Bo; Lei, Tingting; Yan, Yuhong (Frontiers in Psychiatry, 2025)
BackgroundResearch has revealed that presence of meaning in life may be a protective factor for life satisfaction among young adults in China. However, few studies have examined the underlying mechanisms that may mediate or moderate this association. This study aimed to test the mechanisms underlying the relationship between meaning in life and life satisfaction among young adults in China.ObjectiveThis study aimed to examine the effects of presence of meaning in life on the life satisfaction among Chinese young adults, as well as the mediating role of perceived stress and moderating role of hope.MethodsA total of 909 young adults in China completed measures of presence of meaning, perceived stress, hope and life satisfaction. The participants were recruited from four large public universities located in Jiangsu Province in China. SPSS statistical analysis was used to evaluate the relationship between presence of meaning in life, perceived stress, hope and life satisfaction.ResultsPresence of meaning in life was both positively associated with life satisfaction, controlling for grade and being from an urban or rural area (β = 0.46, p < 0.001). Perceived stress played a mediating role in the association between presence of meaning in life and life satisfaction (indirect effect = 0.08, 95%CI = [0.05,0.13]). Furthermore, the interaction of presence of meaning in life and hope was positively related to life satisfaction (β = 0.14, p < 0.01) and the interaction of perceived stress and hope was positively related to life satisfaction (β = 0.11, p < 0.05). A high level of hope can enhance the link between presence of meaning in life and life satisfaction while reduce the link between perceived stress and life satisfaction.ConclusionPresence of meaning in life was positively associated with life satisfaction among Chinese young adults. Furthermore, perceived stress played a mediating role in the association between presence of meaning in life and life satisfaction, and this mediating effect was moderated by hope.